Studies of DNA-interacting properties of certain topological enzymes - Lee, Jasmine Yiqin (2013)
Topoisomerases are topological enzymes that are involved in the regulation of DNA supercoiling. In this thesis, two of the type IIA topoisomerases, Topoisomerase II and DNA Gyrase, will be discussed and their DNA-interacting properties will be studied.